Comparison of personal pronouns in Indonesian and Uzbek languages - Sarieva Zamira (Universitas Muhammadiyah Sidoarjo, 2019)
The role of pronouns is to replace nouns or noun phrases in the sentences. Personal pronouns replace proper and common nouns, so we do not have to repeat them. This article compares personal pronouns in Indonesian and Uzbek languages. The most important point in the analysis is cultural aspect and its influence on the usage of personal pronouns. The article will reveal the influence of such cultural aspects like politeness and kinship based on example of personal pronoun